Computational modeling of meso-scale fracture in polymer matrix composites employing peridynamics. (1st December 2020) - Jenabidehkordi, Ali; Abadi, Rouzbeh; Rabczuk, Timon
Abstract: We present a novel approach for investigating the fracture and mechanical behavior of polymer-matrix composites at the mesoscale. The proposed approach takes advantage of the peridynamics equation of motion and its nonlocality. We show that the approach can predict the fracture behavior and the 'homogenized' stress–strain response which agrees well with experiments. Various volume fractions (in the range between 0.2% to 50%) and particle–matrix stiffness ratios (between 2 to 1000) are considered and the effect of stiffness and the particles density on the mechanical response of the samples are quantified. The particle–matrix stiffness ratio has minimal effect on the fracture behavior of the composite. We find that volume fractions between 15% to 35% improve best the mechanical and fracture response of the composite.